Pengaruh WLB dan Keadilan Organisasi terhadap Loyalitas Karyawan Generasi Z melalui Kepercayaan Organisasi - Rahmawati, Yunita Devi; Prasetyo, Hendy Budi; Arsyad, Nurul Arsyianti; Effendy, Saimon; Yusnita, Irma; Wijaya, Bayu Arya; Girawan, Agi Herdyandyah; Kusumawati, Vita Maya; Hertanto, Robby; Prajogi, Liena; Gunawan, Andreas W (CV. Kalimasada Group, 2025)
This study examines the effects of work–life balance and organizational justice on Generation Z employees’ loyalty, with organizational trust as a mediating variable, within the context of industrial relations at a private security services company in Jakarta. A quantitative approach was employed using an online survey distributed to Generation Z employees. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that work–life balance does not have a significant effect on organizational trust or employee loyalty. In contrast, organizational justice has a positive and significant effect on both organizational trust and employee loyalty. Furthermore, organizational trust does not mediate the relationship between work–life balance and employee loyalty; however, it significantly strengthens the relationship between organizational justice and employee loyalty. These findings suggest that, in a high-pressure and non-conventional work context, perceptions of fairness in procedures, interactions, and resource distribution play a more decisive role in shaping trust and loyalty among Generation Z employees than work–life balance initiatives alone. The study contributes to the organizational behavior literature by highlighting the central role of justice and trust in fostering employee loyalty among younger workforce cohorts and offers practical implications for managerial strategies in similar industrial settings.